Politics and state building in Solomon Islands - Dinnen, Sinclair (2008)
This collection originates in a one-day conference organised jointly by the State Society and Governance in Melanesia (SSGM) Program and the Pacific Centre at the Australian National University on 5 May 2006. The conferenceSolomon Islands, Where to Now?was held shortly after serious disturbances in the Solomon Islands capital, Honiara, in April 2006. This was a timely opportunity to reflect on these events and what they meant for Solomon Islands, as well as for the substantial Australian-led Regional Assistance Mission to Solomon Islands (RAMSI). As well as Australian-based scholars, several colleagues from Solomon Islands and other parts of the region accepted our invitation to contribute their observations and analysis of developments in Honiara. ...